2020
DOI: 10.1016/j.trc.2020.102615
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble deep learning approach for driver lane change intention inference

Abstract: With the rapid development of intelligent vehicles, drivers are increasingly likely to share their control authorities with the intelligent control unit. For building an efficient Advanced Driver Assistance Systems (ADAS) and shared-control systems, the vehicle needs to understand the drivers' intent and their activities to generate assistant and collaborative control strategies. In this study, a driver intention inference system that focuses on the highway lane change maneuvers is proposed. First, a high-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(62 citation statements)
references
References 62 publications
1
54
0
Order By: Relevance
“…We used the approximate normal distribution method to calculate the confidence of the prediction accuracy [ 31 ], and the 95% confidence intervals of recognition accuracy for Int1, Int2 and Int3 were (0.761, 0.825), (0.845, 0.889) and (0.783, 0.849), respectively. The result showed that the accuracy of the driving intention prediction model proposed in this paper was acceptable compared with many existing driving intention prediction algorithms (the prediction accuracy is generally between 75% and 90%) [ 32 , 33 , 34 ].…”
Section: Study 1-a: Driving Intention Prediction Model Based On Hmmentioning
confidence: 76%
“…We used the approximate normal distribution method to calculate the confidence of the prediction accuracy [ 31 ], and the 95% confidence intervals of recognition accuracy for Int1, Int2 and Int3 were (0.761, 0.825), (0.845, 0.889) and (0.783, 0.849), respectively. The result showed that the accuracy of the driving intention prediction model proposed in this paper was acceptable compared with many existing driving intention prediction algorithms (the prediction accuracy is generally between 75% and 90%) [ 32 , 33 , 34 ].…”
Section: Study 1-a: Driving Intention Prediction Model Based On Hmmentioning
confidence: 76%
“…These CI techniques have been used quite successfully in the problem of lane changing. Some studies address precisely the problem of identifying the intent to change lanes, achieving and average intention inference accuracy above 90%, but they usually address the problem using simulators [ 27 ] or few examples in simple environments such as highways [ 28 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these, distracted driving has become an increasingly important cause of traffic accidents in recent years. For example, distracted driving can cause wrong lane changes, which will lead to serious traffic accidents [4] [5]. According to the preliminary definition of the International Organization for Standardization (ISO) [6], distracted driving is "attention given to a non-driving related activity, typically to the detriment of driving performance" The National Highway Traffic Safety Administration (NHTSA) defines distracted driving as "any activity that diverts attention from driving, including talking or texting on the phone, eating and drinking, etc."…”
Section: Introductionmentioning
confidence: 99%